Scalar scattering by black holes and wormholes - Haroldo C. D. Lima Junior; Carolina L. Benone; Luís C. B. Crispino (European Physical Journal C: Particles and Fields, 2022)
Abstract We study the scattering of monochromatic planar scalar waves in a geometry that interpolates between the Schwarzschild solution, regular black holes and traversable wormhole spacetimes. We employ the partial waves approach to compute the differential scattering cross section of the regular black hole, as well as of the wormhole solutions. We compare our full numerical results with the classical geodesic scattering and the glory approximation, obtaining excellent agreement in the appropriate regime of validity of such approximations. We obtain that the differential scattering cross section for the regular black hole case is similar to the Schwarzschild result. Notwithstanding, the results for wormholes can be very distinctive from the black hole ones. In particular, we show that the differential scattering cross section for wormholes considerably decreases at large scattering angles for resonant frequencies.